2019
DOI: 10.3390/catal9090757
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Characteristics of Gas Molecules (H2O, CO2, CO, CH4, and H2) on CaO-Based Catalysts during Biomass Thermal Conversion with in Situ CO2 Capture

Abstract: Biomass thermochemical conversion with in situ CO2 capture is a promising technology in the production of high-quality gas. The adsorption competition mechanism of gas molecules (H2O, CO2, CO, CH4, and H2) on CaO-based catalyst surfaces was studied using density functional theory (DFT) and experimental methods. The adsorption characteristics of CO2 on CaO and 10 wt % Ni/CaO (100) surfaces were investigated in a temperature range of 550–700 °C. The adsorption energies were increased and then weakened, reaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
3
3
0
Order By: Relevance
“…In contrast, the production of CH 4 and CO 2 underwent little change, only exhibiting slight modifications. Due to the marginal improvement in the yield of H 2 and conversion of phenol at 700 • C in comparison with that at 650 • C, alongside observing the highest content of H 2 volume at 650 • C, it was concluded that the most appropriate temperature for catalytic pyrolysis of phenol to hydrogen is 650 • C. This finding is consistent with preceding research [29,30].…”
Section: Effect Of Temperaturesupporting
confidence: 86%
“…In contrast, the production of CH 4 and CO 2 underwent little change, only exhibiting slight modifications. Due to the marginal improvement in the yield of H 2 and conversion of phenol at 700 • C in comparison with that at 650 • C, alongside observing the highest content of H 2 volume at 650 • C, it was concluded that the most appropriate temperature for catalytic pyrolysis of phenol to hydrogen is 650 • C. This finding is consistent with preceding research [29,30].…”
Section: Effect Of Temperaturesupporting
confidence: 86%
“…The basicity of both catalysts was measured by CO 2 -TPD (Figure 5). CaO exhibits a desorption band at 604 °C with a CO 2 uptake of 63.4 μmol CO2 /g cat ascribed to strong basic sites as reported in the literature [34]. BaO exhibits two desorption bands centered at 400 °C and 603 °C, pointing out a combination of sites with moderate and strong basicity.…”
Section: Chemcatchemsupporting
confidence: 72%
“…The N2 adsorption data showed that the SBET, Vtotal, and Vmicro of He-600J and He-800J were significantly lower than those of N2-J and CO2-J prepared at the same temperature, but the difference in CO2 adsorption capacity was small. The main reason was that inert gas He has a strong protective effect, resulting in the surface of He-J chars were rich in hydroxyl, amino and other functional groups, which could improve their adsorption capacity through chemical adsorption [41][42][43][44]. To understand the CO2 adsorption process on MG chars, it was not only necessary to determine the optimal char production atmosphere/temperature but also to investigate the effect of high-temperature desorption on the cyclic regeneration of the products.…”
Section: Co2 Adsorption Experimentsmentioning
confidence: 99%